ASUHAN KEPERAWATAN PADA PASIEN DENGAN INFEKSI NOSOKOMIAL DI RUANG RAWAT ANAK RSU SOE SUATU PENELITIAN KUALITATIF DI KABUPATEN TIMOR TENGAH SELATAN – NUSA TENGGARA TIMUR - Oklan B.T. Liunokas; Florentianus Tat; Namsia Baso; Yublina Rohi; Fransiskus Salesius Onggang; Bringiwatty Batbual; Tri Maryati; Agustina Ina (Journal of Innovation Research and Knowledge, 2025)
Nosocomial infections remain a major challenge in improving the quality of health services, particularly in pediatric wards where patients are more vulnerable. This study aims to explore nurses' experiences in providing nursing care for pediatric patients with nosocomial infections in the Pediatric Ward of Soe Regional General Hospital, Timor Tengah Selatan (TTS), East Nusa Tenggara. A qualitative research approach with a case study design was employed. The main informants consisted of staff nurses, while triangulation informants included physicians, the ward head nurse, and parents of hospitalized children. Data were collected through in-depth interviews, non-participant observations, and document reviews. Data analysis followed Miles and Huberman’s interactive model, including data reduction, data display, and conclusion drawing. The study identified four major themes: (1) nurses’ experiences in caring for children with nosocomial infections; (2) challenges in implementing infection prevention and control (IPC) measures; (3) nurses’ strategies to minimize infection risks; and (4) family involvement in the care process. The findings highlight the need to strengthen nurse competencies, ensure adequate IPC facilities, and promote family engagement to improve pediatric nursing care quality.